Penerapan Metode RAD dalam Perancangan Sistem Informasi Aplikasi Penelusuran Putusan (SIAPP) - Riscy Nuku; Erich Masihor; Rikson Pasaribu (JOINTER : Journal of Informatics Engineering, 2020)
Abstract— The Tondano 1B District Court is one of the courts located in North Sulawesi Province. In the process of taking a copy of the current ruling, the Tondano District Court is still a manual. A copy of the decision itself is very useful because through a copy of the decision, it can be seen the legal reasoning behind the judge's decision in completing a trial. In addition, a copy of the court's decision is also a prerequisite for the parties when they want to file for legal remedies. Because, the main ingredient in compiling appeal or cassation memory is a copy of the decision at the first level. If a copy of the decision does not reach the parties, there is a chance that the opportunity for justice seekers will be lost to submit legal remedies. Because the process is still manual, it requires quite a long time because the case owner must come directly to the Tondano District Court to ask for the availability of a copy of the decision. Then, it is necessary to design an Information System that can facilitate the case and the Tondano District Court in making copies of decisions at the Tondano District Court. This information system is called Sistem Informasi Aplikasi Penelusuran Perkara (SIAPP) and is designed / developed by the Rapid Application Development (RAD) method. With SIAPP, the case party can see the status of the availability of copies of decisions so that they can submit applications for taking copies of decisions from SIAPP and this will save the case and the Tondano District Court time.